SYSTEMATIC LITERATURE REVIEW : STRATEGI PENGEMBANGAN KOMPETENSI APARATUR SIPIL NEGARA MENUJU BIROKRASI MODERN - Indriasari, ratna; Nurdin, Ismail; Erliani, Lia (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2024)
This research aims to conduct a systematic literature review on the competency development strategy of the State Civil Apparatus (ASN) towards modern bureaucracy. Through the collection and analysis of literature for 2020-2024, key findings include increasing ASN creativity, employee empowerment, optimizing information technology, implementing a merit system, developing talent-based human resources, and reforming organizational culture. With effective education and communication, as well as cross-agency collaboration, strategy implementation is expected to create a more modern, responsive, and efficient bureaucracy in providing public services to the community. Keywords: Competency Development, State Civil Apparatus, Modern Bureaucracy